Therapeutic potential of PACAP in alcohol toxicity. (March 2019) - Reglodi, Dora; Toth, Denes; Vicena, Viktoria; Manavalan, Sridharan; Brown, Dwayne; Getachew, Bruk; Tizabi, Yousef
Abstract: Alcohol addiction is a worldwide concern as its detrimental effects go far beyond the addicted individual and can affect the entire family as well as the community. Considerable effort is being expended in understanding the neurobiological basis of such addiction in hope of developing effective prevention and/or intervention strategies. In addition, organ damage and neurotoxicological effects of alcohol are intensely investigated. Pharmacological approaches, so far, have only provided partial success in prevention or treatment of alcohol use disorder (AUD) including the neurotoxicological consequences of heavy drinking. Pituitary adenylate cyclase-activating polypeptide (PACAP) is an endogenous 38 amino-acid neuropeptide with demonstrated protection against neuronal injury, trauma as well as various endogenous and exogenous toxic agents including alcohol. In this mini-review, following a brief presentation of alcohol addiction and its neurotoxicity, the potential of PACAP as a therapeutic intervention in toxicological consequences of this devastating disorder is discussed. Highlights: PACAP is distributed in brain areas involved in addiction. PACAP protects against ethanol toxicity in neuroblastoma and cerebellar cells in vitro. PACAP has neuroprotective effects against alcohol-induced toxicity in vivo.